Peningkatan Hasil Belajar Tari Siswa Menggunakan Model Pembelajaran TAGUNTA Di Kelas III SDN 29 Ganting Utara Kota Padang - Indah Mutiara Sani; Yuliasma Yuliasma (FBS Universitas Negeri Padang, 2022)
This research was motivated by the low mastery of students in learning dance practice which resulted in students' dance learning outcomes not reaching the Minimum Completeness Criteria (KKM) in class III SDN 29 Ganting Utara, Padang City. This study aims to improve student dance learning outcomes at SDN 29 Ganting Utara, Padang City. This type of research is classroom action research. The subjects in this study were class III.b students of SN 29 North Ganting, Padang City who were registered in the 2021/2022 academic year which consisted of 22 students. The results showed that the use of the TAGUNTA learning model in dance learning was able to improve student learning outcomes, enthusiasm, and student activity in learning activities, this could be seen from the increase in student activities and learning outcomes in each meeting. Student activity in the first cycle amounted to 67% and in the second cycle student activity greatly increased to 92.1%. Then it was found that the students' dance learning outcomes in the first cycle were by looking at the students' cognitive abilities (knowledge) and students' practical (psychomotor) abilities. Student learning outcomes after the written test obtained an average score of 84% while the average practical (psychomotor) ability of students was 45%, the two tests were added up so that it became an average of 64.5% with quite good criteria. Then in the second cycle, student learning outcomes according to the indiators increased to obtain an average percentage of 84% with good criteria. Thus, it can be concluded that the application of the TAGUNTA learning model can improve student dance learning outcomes at SDN 29 Ganting Utara, Padang City.